Identifying and Addressing Critical Issues in the Indian Construction Industry: Perspectives of Large Building Construction Clients - Loganathan, Santhosh; Srinath, Purushothaman; Kumaraswamy, Mohan; Kalidindi, Satyanarayana; Varghese, Koshy (Penerbit Universiti Sains Malaysia, 2017)
The Indian construction industry faces increasing challenges amidst serious performance shortfalls. Confronting similar issues in past decades, other countries such as the UK, USA, and Singapore commissioned high-powered studies and set up industry development bodies to address their own priorities. Initiatives in other countries are brieﬂy reviewed before outlining the launch of the “Construction Industry Improvement Initiative India” (Ci3 India) that aims to address our own challenges. This paper focuses on identifying and launching a platform to address the current and imminent critical issues in the Indian Construction Industry. Nineteen critical issues were identifed, verifed, and validated through four focus group sessions at two Regional Roundtables with 54 high calibre large building construction clients, academicians, and other invited experts. The identifed issues were consolidated to 10 Action Items. Seven Action Teams were then mobilized to work on the 10 Action Items. Having consolidated a base consensus of clients on the way forward, it was also proposed to develop a “Construction Clients’ Charter” that will set out basic principles, protocols, and targeted good practices by lead clients, who by voluntarily agreeing and implementing these together, could catalyse signifcant industry improvements